Three-Dimensional Printing and Its Impact on the Diagnosis and Treatment of Neurodegenerative Disease - Sameer Patil; Ami Thakkar; Ginpreet Kaur; Amisha Vora; Ritu Chauhan; Seema Ramniwas; Abhishek Chauhan; Damandeep Kaur; Hardeep Singh Tuli (Biophysica)
Neurodegenerative disorders include Alzheimer’s and Parkinson’s, both of which lead to progressive loss of neurons resulting in the severe loss of cognitive and motor functions. These diseases are among the heavy burdens on global healthcare systems largely because there is no cure, and current treatments apply almost entirely to controlling symptoms rather than disease progression. Recent advances in 3D printing and bioprinting technologies now open the way to overcome these challenges and form patient-specific models and therapeutical tools closely simulating the complex environment of the human brain. It then further illustrates how this technological integration with the aid of 3D printing, coupled with microfabrication and biosensing technologies, transforms drug-screening platforms as well as develops customization in medicine. For example, one can form highly intricate and multi-materially composed structures to better facilitate one’s study or test into some new therapeutic possibilities using methodologies of stereolithography and selective laser sintering. Moreover, 3D printing allows the creation of organ-on-a-chip models that simulate brain-like conditions, which may help identify specific biomarkers and evaluate new options of therapy. On the other hand, bioprinting methods based on neural cells combined with scaffolds mimicking native tissue dramatically transform regenerative medicine. New pathways in neural tissue development and implantable devices are now being brought forth, which can be tailored to the needs of individual patients. These advances bring not only greater precision in terms of the therapy that can be delivered but also 3D printing of implantable microelectrodes able to determine real-time biomarkers responsible for neurodegenerative diseases. Thus, this review highlights the robust impact that might be brought forth on the diagnosis and treatment of these neurodegenerative diseases via 3D printing technologies toward more effective management and personal solutions for healthcare.